Les implications éthiques de l'accompagnement doctoral - Maryvonne Charmillot
"To be with and to go towards" is the minimal definition of the verb to accompany. This perspective makes accompaniment a particular relationship based on the symbolic value of sharing (Paul, 2009). Talking about doctoral accompaniment thus marks a strong conceptual positioning. What are the ethical implications of such an approach and how can they be identified? This contribution addresses this question from an epistemological perspective. The hypothesis suggested is that despite the ethical charters of the doctorate that define the contours of supervision or more broadly of doctoral training and despite academic freedom determined as a general principle of university research, a blind spot linked to epistemological questions remains. Doctoral students are confronted with gaps in meaning and may feel alone, isolated, or even in distress. This contribution proposes to update the ethical implications of doctoral accompaniment by recognising the political dimension of knowledge, by putting the responsibility of researchers back at the centre, by encouraging commitment and by valuing the biographical dimension in the construction of knowledge. These implications are illustrated by examples of insolent acts of research in response to certain positivist injunctions that put doctoral students in difficulty.